The development of the research on the history of libraries: a handful of reflections from the French perspective - Jean-Dominique Mellot (Biblioteka)
Studies on the history of libraries as a research field within a domain of the French historiographic tradition first appeared towards the end of the 1980s. Its theoretical underpinnings were in fact provided by the existing studies on the history of books and the founding works by Henri-Jean Martin (1924–2007). Despite a sizeable number of publications following the publication of the Histoire des bibliothèques françaises (Paris, 1988–1992, 4 vols.), this particular research area somehow failed to take advantage of the dynamics generally attributed to works on the history of books. Largely focusing on institutional and present-day issues, a substantial portion of the study on the history of libraries continued for a long time to be isolated and dominated by library-based authors only. A change in this situation came as late as the first decade of the 21st century and was greatly influenced by the works of the recently deceased historian Frédéric Barbier (1952–2023). Since that time, we have been witnessing a significant widening of perspectives, very much in line with the wish expressed by F. Barbier himself in his Histoire des bibliothèques en Occident (ed. I, Paris, 2013). This area of research (history of libraries) attracts interests of more and more researchers and has become a transnational domain at the pan-European level. The present research study documents these cultural and timeless transitions (challenging the perceived divisions between the Middle Ages and the Ancien Régime, and the Ancien Régime and modern times), and thus becoming multidisciplinary as well as interdisciplinary studies that integrate a number of disciplines (political history, social history, history of culture, architecture, etc.). At the same time, research on the history of libraries retains a strong relationship with studies on the history of books and media. The position and standing of libraries, that went through profound transformations due to both cuts in their budgets and the implications of the digital revolution in the first years of the 21st century, seems to be endangered, both as an institution and a place. However, their purpose in modern democracy is not outdated and they still perform a significant mission by making it possible for all to have equal access to cultural resources and media. Libraries provide non-vertical mediation (i.e. cataloguing and metadata creation, classification and storage …), that is still essential to make data and documents available. They continue to accommodate in one cultural space – that becomes more and more comfortable and friendly – both readers and visitors that learn to “live together” within this space, conforming at the same time to applicable rules and regulations. Despite their seemingly disadvantageous situation, one may though assume that modern libraries will continue to provide fresh and stimulating material for historical research for long years to come